2006
DOI: 10.1016/j.pain.2006.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Pain activates cortical areas in the preterm newborn brain

Abstract: To study the patterns of supraspinal pain processing in neonates, we hypothesized that acute pain causes haemodynamic changes associated with activation of the primary somatosensory cortex. Forty preterm neonates at 28-36 weeks of gestation (mean=32.0) and at 25-42 h (mean=30.7) of age were studied following standardized tactile (skin disinfection) and painful (venipuncture) stimuli. Changes in regional cerebral haemodynamics were monitored by near infrared spectroscopy (NIRS) over both somatosensory cortices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
305
2
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 452 publications
(342 citation statements)
references
References 62 publications
24
305
2
11
Order By: Relevance
“…Comparable to the results in the present study, awake subjects reacted more to the stimulus (29). Together with the findings by Fernandez et al, these studies suggest the presence of a transient and delayed (ÏŸ10 s) electrographic (EEG) or hemodynamic (NIRS) response to pain stimuli (10,28,29).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Comparable to the results in the present study, awake subjects reacted more to the stimulus (29). Together with the findings by Fernandez et al, these studies suggest the presence of a transient and delayed (ÏŸ10 s) electrographic (EEG) or hemodynamic (NIRS) response to pain stimuli (10,28,29).…”
Section: Discussionsupporting
confidence: 85%
“…Such EEG activation might be of long latency and long lasting and could be associated with changes in cerebral blood flow. Hemodynamic responses to pain were evaluated by near infrared spectroscopy (NIRS) in newborn infants, an increase in oxygenated Hb was found over the central cortical regions (28,29). Comparable to the results in the present study, awake subjects reacted more to the stimulus (29).…”
Section: Discussionsupporting
confidence: 57%
“…Interestingly, the cortical responses to noxious stimulation were found to be greater in awake than in sleeping infants (39). Moreover, the bilateral activation noticed in the Bartocci et al (40) study was suggested to include the S 2 cortex, anterior insula, ventral premotor area, and anterior cingulate cortex which belong to the GNW circuits.…”
Section: Sensory Perceptionmentioning
confidence: 85%
“…Exposure to repetitive or prolonged pain occurs during critical periods of brain development in preterm neonates (8,22), which may alter the structure and function of their developing brains (23,24). Brief inflammatory pain in the right forepaw led to bilateral increases in neuronal activation, with a shift from subcortical to cortical processing between P7 and P14, and to increased cell death occurring more prominently at P1 and P7 than at P14.…”
Section: Discussionmentioning
confidence: 99%